RV568, a narrow-spectrum kinase inhibitor with p38 MAPK-α and -γ selectivity, suppresses COPD inflammation. Issue 4 (26th October 2017) - Charron, Catherine E.; Russell, Paul; Ito, Kazuhiro; Lea, Simon; Kizawa, Yasuo; Brindley, Charlie; Singh, Dave
Novel anti-inflammatory approaches targeting chronically activated kinase pathways in chronic obstructive pulmonary disease (COPD) are needed. We evaluated RV568, a p38 mitogen-activated protein kinase-α and -γ and SRC family kinase inhibitor, in cellular and in vivo models relevant to COPD and examined its safety and efficacy in COPD patients. The anti-inflammatory activities of RV568 were tested in primary cultured monocytes, macrophages and bronchial epithelial cells and in vivo in lipopolysaccharide and cigarette smoke-exposed murine models. RV568 was evaluated in a 14-day trial in COPD patients. RV568 showed potent anti-inflammatory effects in monocytes and macrophages, which were often greater than those of corticosteroids or the p38 inhibitor Birb796. RV568 combined with corticosteroid had anti-inflammatory effects suggestive of a synergistic interaction in poly I:C-stimulated BEAS-2B cells and in the cigarette smoke model. In COPD patients, inhaled RV568 (50 µg and 100 µg) improved pre-bronchodilator forced expiratory volume in 1 s (69 mL and 48 mL respectively) and significantly reduced sputum malondialdehyde (p<0.05) compared to placebo, although there were no changes in sputum cell counts. Adverse events during RV568 and placebo treatment were similar. RV568 shows potent anti-inflammatory effects on cell and animal models relevant to COPD. RV568 was well-tolerated and demonstrated a modest clinical benefit in a 14-day COPD clinical trial. Kinase inhibitor RV568 is anti-inflammatory in COPD models and shows signs of clinical efficacy in a small trial http://ow.ly/aASJ30fjOQL